Harmonic mitigation project, Work Package 2: Algorithm design, development and implementation for single inverter control - Atheer Habash (2020)
The work reported here describes Work Package 2 (WP2) of the WPD NIA Harmonic Mitigation project: the development and validation of a control algorithm to provide existing PV inverters with active filter (AF) functionality. The AF functionality is in addition to the main task performed by these devices, i.e. the delivery of power from the photovoltaic panels to the power grid. The chosen modelling environment for this work is MATLAB/Simulink. A detailed model of the PV inverters and power system under consideration has been built and validated as part of Work Package 1 (WP1). The harmonic mitigation algorithm was iteratively developed and tested within this modelling environment, and the resulting impact of operating the algorithm was also demonstrated using this environment. The development of the AF functionality consisted of determining appropriate control algorithms and parameters that allow the PV inverter to inject harmonic components equal in magnitude and opposite in phase with respect to existing harmonics on the feeder. As a result, cancellation of harmonic currents is obtained, leading to reduced harmonic voltage distortion in the upstream network. The principle features of the algorithm are described in Section 2.1 of the slide pack accompanying this summary, together with key issues that shaped the algorithm’s development (Section 2.2).The proposed algorithm was tested with varying harmonic levels, varying levels of irradiance, and for balanced and unbalanced harmonic currents. Additional controls were introduced to ensure that the rating of the PV inverter is not exceeded when harmonics are injected, and to avoid significant and frequent swings in the level of instructed harmonic mitigation.